The role of different PI-RADS versions in prostate multiparametric magnetic resonance tomography assessment - Aliukonis, Paulius; Letauta, Tadas; Briedienė, Rūta; Naruševičiūtė, Ieva; Letautienė, Simona (Acta medica Lituanica, 2017)
Background. Standardised Prostate Imaging Reporting and Data System (PI-RADS) guidelines for the assessment of prostate alterations were designed for the assessment of prostate pathology. Published by the ESUR in 2012, PI-RADS v1 was based on the total score of different MRI sequences with subsequent calculation. PI-RADS v2 was published by the American College of Radiology in 2015 and featured different assessment criteria for prostate peripheral and transitory zones. Aim. To assess the correlations of PI-RADS v1 and PI-RADS v2 with Gleason score values and to define their predictive values of the diagnosis of prostate cancer. Materials and methods. A  retrospective analysis of 66 patients. Prostate specific antigen (PSA) value and the  Gleason score (GS) were assessed. One the most malignant focal lesion was selected in the peripheral zone of each lobe of the prostate (91 in total). Statistical analysis was carried out applying SPSS software, v.23, p
Keywords: prostate; malignant; cancer; multiparametric; MRI; PI-RADS